PMAP – smart and sustainable in situ treatment of mine wastewater and critical metals recovery technology - M Barkh; F X. Spachtholz (The Australasian Institute of Mining and Metallurgy, 2024)
The mining industry faces significant environmental challenges in managing tailing ponds and wastewater treatment, including the risk of contaminated water, breaches of tailing dams, and energy-intensive treatment processes. Traditional methods involve pumping water to secondary treatment facilities for neutralisation, which is costly and poses operational and environmental risks. In response to these challenges, the Professional Mine Water Action Plan (PMAP) introduces a revolutionary approach that combines cutting-edge AI technology and environmentally friendly reagents for in situ neutralisation of acidic wastewater. PMAP leverages magnesium-based slowrelease reagents and AI-driven intelligent dispensing systems to optimise treatment processes within the tailing pond itself. The unmanned smart dispensing vessel (USDV) conducts bathymetry to gather data on water quality and hydrography, allowing the system to determine the appropriate reagent quantity and injection strategy. This approach transforms the tailing pond into virtual reaction columns, enabling individual and simultaneous water treatment while optimising efficiency. PMAP’s novel reagent demonstrates exceptional efficacy in removing critical metals like cobalt, nickel, and copper, as well as reducing harmful metals such as mercury and manganese to undetectable concentrations. Unlike traditional lime-based treatments, PMAP’s reagent prevents gypsum formation and reduces waste volume significantly, improving reagent utilisation and solid waste handling. Furthermore, PMAP technology offers benefits beyond environmental stewardship. By reducing water treatment costs and improving resource management, it enhances operational efficiency and aligns with broader corporate sustainability goals. Additionally, PMAP expedites permitting processes by eliminating the need for traditional water treatment infrastructure and mitigating risks associated with hazardous reagent transportation. Integrating PMAP as a pre-treatment for existing lime facilities provides further benefits, including optimisation of treatment operations, reduced reagent consumption, and the recovery of valuable metals from generated sludges. Overall, PMAP represents a groundbreaking advancement in mining wastewater management, showcasing the transformative potential of AI and environmentally friendly solutions to foster sustainable and responsible mining practices globally. Its inaugural project in the Yukon Territory aims to demonstrate its capability to remove contaminants from mine water, paving the way for widespread adoption in the industry.